LAPAROSCOPIC ASSISTED APPENDECTOMY IN CHILDREN. OUR EXPERIENCE OF FIRST 50 CASES AT TERTIARY CARE HOSPITAL RAWALPINDI: Laparoscopic Assisted Appendectomy in Children - Ahmed, Waqas; Ahmed, Iftikhar; Ibrahim, Taseer; Awan, Safdar Hussain; Fraz, Omer; Safdar, Chaudhary Aqeel (Pakistan Armed Forces Medical Journal, 2018)
Objective: To present an experience of the first 50 cases of appendectomy performed via laparoscopy assisted open technique. Study Design: Descriptive case series. Place and Duration of Study: This study was carried out at Pediatric Surgery department, Pak Emirates Military Hospital Rawalpindi, from Jan 2016 to Apr 2018. Material and Methods: Fifty patients (<12 years old) diagnosed as cases of acute appendicitis were enrolled after ethical committee approval. The procedure was performed via three ports (4 ports if required). Appendix was brought out through the right iliac fossa port and appendectomy was performed by extracorporeal knotting technique. Operative time, position of appendix and postoperative complications were recorded. Data was expressed as means and frequency percentages. Results: Out of 50 patients, 31 were male and 19 were females. The mean age of the patients was 7.99 ± 3.34 years. Forty one patients had acute appendicitis while 9 patients were diagnosed as appendicular mass. The mean operative time was 24.9 ± 7.42 minutes. There were no cases of surgical site infection. Thirty eight patients were operated via three ports while 12 patients required four ports. Three patients required conversion to open appendicectomy due to extensive adhesions or abscess. Post-operatively drain was placed in only 6 patients. Conclusion: Laparoscopic assisted open appendectomy is a safe, quick and easy to learn technique in children which combines all the advantages of minimal access surgery with open appendectomy while reducing the number of complications associated with it. The technique has the added advantage of diagnostic laparoscopy over open surgery.